The post-scarcity world and the post-pandemic office - Mehra, Salil K. (Frontiers in Research Metrics and Analytics, 2022)
We are not yet in the post-scarcity world that John Maynard Keynes famously envisioned, and vaccines have only recently allowed us to hope that a post-COVID-19 future may arrive soon. However, it is not too early to consider the impact of both on the traditional office, and on attempts to bring it back for reasons that may be socially harmful. One lesson of the pandemic is that many workers can be as—or even more—productive working from home, thanks chiefly to software such as Zoom, Microsoft Teams, and Slack, among others, which enable better collaboration across distances than was previously possible. At the turn of the century, we moved toward an economy in which important products were increasingly characterized by low marginal costs of production, such as pharmaceuticals and software. Over the past decade, we have seen fixed costs reduced in some situations—consider how Uber greatly eliminates the need for a central taxi dispatcher, and makes use of idle capital invested in personal vehicles. The traditional office represents a massive fixed cost for many industries; tech-driven work-from-home greatly reduces the need for this fixed cost. While software, Internet connectivity and the cloud are not free, preliminary estimates suggest that replacing traditional offices with work-from-home greatly lowers costs, creates economic efficiencies and, relatedly, reduces environmental harm. That said, the story of work-from-home is not one of unbridled optimism. Real estate firms and local governments are already trying to use law as a tool to return workers to the pre-pandemic traditional office. Various levels of government seek to return workers to physical offices, often motivated by declines in tax receipts. Attempts to bolster a return to the traditional office may raise fixed costs for firms and generate substantial avoidable environmental damage. This Chapter recommends competition advocacy to counterbalance state and local attempts to prevent the efficient disruption of the traditional office's fixed costs. Work-from-home represents an important step toward the post-scarcity world; but without a focus on what amounts to state-and-local protectionism in this sphere, we could wind up taking another step backwards.